Implementation Of Flashcard Media In Increasing Students' Interest In Learning Mufrodat In Learning Arabic - Ainun Shofiyatu Az Zahrah; Muh Barid Nizarudin Wajdi (IERA, Islamic Education and Research Academy, 2024)
This study explores the implementation of flashcard media in Arabic language learning to enhance the vocabulary learning interest (mufrodat) of eighth-grade students at MTs Darul Muta'allimin Patianrowo. Flashcards, as visual learning aids, have been identified as effective tools for engaging students and improving their retention of new vocabulary. The research employs a qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the use of flashcards significantly increases students' interest in learning Arabic vocabulary, leading to improved comprehension and retention. The study also identifies both supporting factors, such as the availability of teaching resources, and challenges, including diverse student backgrounds and varying levels of motivation. The implementation of flashcards has been shown to create a more dynamic and interactive learning environment, ultimately enhancing students' vocabulary acquisition.